APLIKASI PENILAIAN NILAI SISWA SMA NEGERI 4 SAMARINDA BERBASIS WEB - Bonaventura Welan; Damar Nucahyono; Bambang Cahyono (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Samarinda State High School 4, as an educational institution committed to improving the quality of educational services, faces challenges in managing student grades, a process that is still carried out manually. This manual process is often time-consuming and prone to errors. In addition, students’ access to information regarding their academic progress is limited. This research was conducted with the aim of improving the efficiency and effectiveness of managing academic data for both students and teachers. This application is designed to make it easier for teachers to enter and manage student grades, as well as to provide students with better access to monitor their academic progress. The method used in designing this application is the Waterfall Method, whose stages include requirements analysis, system design, implementation, application testing, and maintenance. This application was developed using Visual Studio Code as the IDE with the PHP programming language and utilizes MySQL as the database to store data. Application testing was conducted using Alpha Testing via the Blackbox Testing Method, which showed that all major features in the system functioned properly, with no errors found.